2011
DOI: 10.1002/pbc.24031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of acute chemotherapy‐associated toxicity in patients with Ewing sarcoma

Abstract: Background Ewing sarcoma (ES) is a malignant tumor of bone and soft tissue of children and young adults. Patients with ES are treated with intensive chemotherapy regimens. We describe predictors of acute chemotherapy-associated toxicity in this population. Procedure In this retrospective cohort study, records of ES patients treated at two academic medical centers between 1980 and 2010 were reviewed. Grade 3 and 4 non-hematologic chemotherapy-associated toxicities during frontline therapy were recorded for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 34 publications
2
24
0
7
Order By: Relevance
“…Moreover, our patients were very compliant and therefore received the recommended chemotherapy with no difference between preadolescents and older patients with regard to chemoreduction for toxicities. There is a recent report by Sharib et al18 that mentioned increased toxicity in young patients and in their Latino population with Ewing Sarcoma. We did not find an increase in toxicity in either of these groups within our cohort and thus could not use it as an explanation for the trend toward inferior outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our patients were very compliant and therefore received the recommended chemotherapy with no difference between preadolescents and older patients with regard to chemoreduction for toxicities. There is a recent report by Sharib et al18 that mentioned increased toxicity in young patients and in their Latino population with Ewing Sarcoma. We did not find an increase in toxicity in either of these groups within our cohort and thus could not use it as an explanation for the trend toward inferior outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Among adolescent/young adults with Ewing sarcoma, osteosarcoma, and Hodgkin lymphoma, Khamly and co‐workers found chemotherapy both more toxic (greater neutropenia and transfusion use) and more effective for female patients . In contrast, Sharib and co‐workers found no male/female differences in treatment‐related toxicities among Ewing sarcoma patients (n = 142). Some of the above studies suggest a positive relationship between toxicities and treatment outcome, a relationship that is intriguing considering the differences in toxicities found for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear from the available registry data whether these early deaths are due to early disease progression or due to the toxicity of the intensive therapies used to treat this disease. At least one previous report found that younger age was associated with increased therapy‐associated toxicity, although young patients in that analysis included all patients <12 years of age . However, our finding that infants who did not receive surgery had significantly inferior outcomes suggests that difficulty attaining adequate local control may be partially responsible for these early failures.…”
Section: Discussionmentioning
confidence: 67%
“…At least one previous report found that younger age was associated with increased therapy-associated toxicity, although young patients in that analysis included all patients <12 years of age. [35] However, our finding that infants who did not receive surgery had significantly inferior outcomes suggests that difficulty attaining adequate local control may be partially responsible for these early failures. The observed trend indicating lower survival in patients not treated with radiation supports this hypothesis.…”
Section: Discussionmentioning
confidence: 83%